Remote Work Environment and Employee Performance in the Digital Era - Maghfur, Abdul Aziz; Isnanto, Samto Hadi (Dinasti International Journal of Management Science, 2025)
The digital era has driven significant changes in work paradigms, particularly with the increasing adoption of remote work environments. This study aims to analyze the impact of remote work environments on employee performance by considering factors such as motivation, technology utilization, and work-life balance. Using a qualitative approach based on literature studies, this research finds that technological adaptation, enhanced digital competencies, and human-machine collaboration play crucial roles in improving employee performance. Additionally, adaptive leadership and an organizational culture that supports innovation are key factors in addressing remote work challenges, such as social isolation and team coordination difficulties. The findings of this study indicate that effective human resource management strategies, including continuous training and flexible work policies, can help improve productivity and employee well-being in remote work settings.